Phytoestrogens Enhance the Vascular Actions of the Endocannabinoid Anandamide in Mesenteric Beds of Female Rats - Roxana N. Peroni; Tamara Abramoff; Isabel Neuman; Ernesto J. Podestá; Edda Adler-Graschinsky (International Journal of Hypertension)
In rat isolated mesenteric beds that were contracted with NA as an in vitro model of the vascular adrenergic hyperactivity that usually precedes the onset of primary hypertension, the oral administration (3 daily doses) of either 10 mg/kg genistein or 20 mg/kg daidzein potentiated the anandamide-induced reduction of contractility to NA in female but not in male rats. Oral treatment with phytoestrogens also restored the vascular effects of anandamide as well as the mesenteric content of calcitonin gene-related peptide (CGRP) that were reduced after ovariectomy. The enhancement of anandamide effects caused by phytoestrogens was prevented by the concomitant administration of the estrogen receptor antagonist fulvestrant (2.5 mg/kg, s.c., 3 daily doses). It is concluded that, in the vasculature of female rats, phytoestrogens produced an estrogen-receptor-dependent enhancement of the anandamide-vascular actions that involves the modulation of CGRP levels and appears to be relevant whenever an adrenergic hyperactivity occurs.